Assessment of functional outcome of operative vs conservative management of displaced clavicle fractures - Singh, Harpreet; Saoji, Krushna; Tyagi, Sangam; Patel, Dhruv; Patel, Parth; Patel, Tilak (International Journal of Research in Orthopaedics, 2021)
Background: clavicle fractures account for approximately 2.6% of all fractures. Middle third fractures account for 80% of all clavicle fractures. Historically, clavicle fractures have been treated mostly nonoperatively with clavicular brace, but due to increase rate of complications such as nonunion and malunion, clavicle fractures are now increasingly being treated surgically which results in lower rate of such complications, besides improved patient oriented outcome and early mobilization. Methods: Current study is a prospective and observational comparative study, conducted over 30 patients diagnosed with displaced clavicle fractures coming to the department of orthopaedics in a tertiary care hospital in South Rajashthan between January 2019 to June 2020. Patients were then allotted alternatively into two groups. Patients selected for conservative treatment were treated with the figure of eight clavicle brace and arm sling pouch. Patients selected for operative treatment were treated with plating. Functional outcomes were assessed using Constant and Murley score in every follow up at 3 month and 6 month; and fracture union was assessed by serial radiographs taken at sixth week, third month and sixth month. Results: Among 30 patients, 15 patients were treated conservatively and rest 15 patients were treated surgically with plating. Functional outcome at the end of third and sixth months of follow up were measured by using Constant Murley score and found significantly higher in operative group than conservative group. Conclusions: In our study, it was found that at the end of 6 month follow up, patients treated surgically with plating had better functional outcomes than conservatively treated patients as measured by Constant and Murley score. It was also seen that, the duration of union and the incidence of complications was less in the operative group as compared to the conservative group.